Diseño arquitectónico de un centro de rehabilitación física en Guayaquil - Calderón Choez, Brenda Zulay (2024)
Currently, the population of people with injuries and physical disabilities has been increasing significantly, which has caused the demand for facilities that offer physiotherapy services to increase. However, the reality of these establishments is different, as the number of these centers is minimal due to the inadequate facilities in which they decide to provide this type of treatment. This project is focused on presenting a solution through the design of a physical rehabilitation center in the Kennedy sector of the city of Guayaquil, which aims to provide spaces that not only provide physiotherapy care, but also respond to the needs of this population group that in many cases have been vulnerable due to not having adequate spaces. This project involves a series of important procedures and phases, such as previous studies and analyses on the user to whom this project is directed, a detailed diagnosis and how the design and its materiality are developed, at this point basically the entire design process is included, considering that the proposed space must not only be striking, but also but it must also comply with functionality, providing spaces that encourage activity between patients and the environment that surrounds them. Finally, the resulting design will be based on responding to the problem, giving importance and priority to the user through a quality service with respect to physical rehabilitation and all that it entails.